MENINGKATKAN MOTIVASI BELAJAR PENDIDIKAN AGAM ISLAM “BERIMAN KEPADA QODO DAN QODAR” DENGAN METODE PENDEKATAN BERBASIS AKTIVITAS PADA SISWA KELAS VI SEKOLAH DASAR NEGERI 018 KECAMATAN RAMBAH KABUPATEN ROKAN HULU - Erniza Gazali (Indonesian Journal of Basic Education, 2019)
This research is a classroom action research aimed at increasing the motivation and learning activities of the Islamic religion. The results of the study show that the learning strategy with an Activity-Based Teaching Approach in the Learning of Islamic Education in Class VI Students at SD N 018 Rambah Kec. Explore the Rokan Hulu Regency for the 2017/2018 Academic Year can increase motivation, achievement, creativity, and problem solving in learning. The learning strategy by using learning strategies based on activity can increase learning motivation of Class VI students at SD N 018 Explore the Rokan Hulu District 2014/2015 Academic Year on the subject of Islamic Education, the subject of Bertatakrama in Daily Life.